2015
DOI: 10.1038/srep16842
|View full text |Cite
|
Sign up to set email alerts
|

Efficient long-term survival of cell grafts after myocardial infarction with thick viable cardiac tissue entirely from pluripotent stem cells

Abstract: Poor engraftment of cells after transplantation to the heart is a common and unresolved problem in the cardiac cell therapies. We previously generated cardiovascular cell sheets entirely from pluripotent stem cells with cardiomyocytes, endothelial cells and vascular mural cells. Though sheet transplantation showed a better engraftment and improved cardiac function after myocardial infarction, stacking limitation (up to 3 sheets) by hypoxia hampered larger structure formation and long-term survival of the graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 48 publications
(94 reference statements)
0
66
0
Order By: Relevance
“…ECTs were incubated with staining solution (50 mL/L Ethidium Homodimer III and 50 mL/L Hoechst 33342, PromoCell GmbH, Heidelberg, Germany) in a pH-adjusted buffer for 60 minutes at room temperature and protected from light22. Fluorescent images were obtained using an Olympus DP72 optical microscope (Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ECTs were incubated with staining solution (50 mL/L Ethidium Homodimer III and 50 mL/L Hoechst 33342, PromoCell GmbH, Heidelberg, Germany) in a pH-adjusted buffer for 60 minutes at room temperature and protected from light22. Fluorescent images were obtained using an Olympus DP72 optical microscope (Olympus, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Several ECT scale-up strategies have been described including pre-vascularization2021, stacking cell sheets22, scalable scaffolds23, and bioprinting24. Guided by initial works from the Bursac lab using Polydimethylsiloxane (PDMS) molds to form porous engineered tissues from neonatal rat skeletal myoblasts and CMs25, human ESC-derived CMs26, and mouse iPSCs27, we fabricated a range of mold geometries from 0.5mm thick PDMS sheets.…”
mentioning
confidence: 99%
“…p38 MAPK, a major member of the MAPKs, has been shown to play a vital role in the development of cardiac fibrosis, MI, and cardiac hypertrophy4. Recent studies have suggested the involvement of the AT1R/p38 MAPK pathway in pancreatic fibrosis5, renal tubulointerstitial fibrosis6, and peritoneal fibrosis7.…”
mentioning
confidence: 99%
“…Therefore, in vitro cell-dense tissues with the desired thickness can be fabricated by multiple cell sheet layering. Additionally, Matsuo et al inserted gelatin hydrogel microspheres (GHMs) between each cardiovascular cell sheet to break the viability limitation via appropriate spacing and fluid impregnation with GHMs [86]. Fifteen sheets with GHMs (> 1 mm thickness) were stacked within several hours and viable after 1 week in vitro.…”
Section: Cell Sheet-based Cardiac Engineeringmentioning
confidence: 99%